Flourishing: American Indian Positive Mental Health. (November 2015) - Kading, Margarette L.; Hautala, Dane S.; Palombi, Laura C.; Aronson, Benjamin D.; Smith, Reid C.; Walls, Melissa L.
Positive mental health (PMH) is an important construct for understanding the full continuum of mental health. Some socially disadvantaged populations experience a paradoxically high level of PMH despite negative social experiences including discrimination. The purpose of this study is to examine the prevalence and culturally salient correlates of PMH among a cross-sectional sample of 218 American Indian adults living with type 2 diabetes mellitus. Although 17.1 percent of individuals in this sample met Patient Health Questionnaire (PHQ-9) criteria for depression, 51.5 percent were in flourishing PMH. Perceived discrimination was negatively associated with PMH, and participation in traditional cultural activities was positively associated with PMH. Traditional cultural activities did not appear to buffer the impact of discrimination on PMH. This study contributes to strengths-based research with American Indian communities, furthers our understanding of correlates of PMH, and documents comparatively high rates of flourishing mental health in our sample relative to previously published studies with diverse samples.